Strategic Association European Union-Latin America: Birregional rela-tions with variable geometry? - Europea, Comisión (2010)
In recent years, Brazil's role in the global landscape has been increasingly important and has revealed itself as a key interlocutor for the European Union (EU). However, until very recently, the EU-Brazil dialogue has not been sufficiently exploited, which has taken place mainly through the EU-Southern Common Market (MERCOSUR) dialogue. Brazil will be the last “BRICS” to meet with the EU at a summit. The time has come to consider this strategic partner country and important economic actor and Latin American regional leader.